1983
DOI: 10.1002/clc.4960060407
|View full text |Cite
|
Sign up to set email alerts
|

Acute amphetamine cardiomyopathy in a drug addict

Abstract: Summary: A case of acute left ventricular failure following an intravenous dose of amphetamine is described. The diagnosis was made by right heart catheterization. This is the first description of acute amphetamine cardiomyopathy in the medical literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 7 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Since single doses of PPA that cause myocardial necrosis in rats are comparable to doses that have caused such injury in humans, this animal model likely has clinical relevance with respect to the pattern of toxicity manifested in humans (9). It is also noteworthy that a similar microscopic myocardial injury pattern has been described for patients with pheochromocytoma and amphetamine-associated cardiomyopathy (12,14,15).…”
Section: Phentolamine Reduces Myocardial Injury and Mortality 133mentioning
confidence: 84%
“…Since single doses of PPA that cause myocardial necrosis in rats are comparable to doses that have caused such injury in humans, this animal model likely has clinical relevance with respect to the pattern of toxicity manifested in humans (9). It is also noteworthy that a similar microscopic myocardial injury pattern has been described for patients with pheochromocytoma and amphetamine-associated cardiomyopathy (12,14,15).…”
Section: Phentolamine Reduces Myocardial Injury and Mortality 133mentioning
confidence: 84%
“…On at least one occasion the degree of left ventricular failure was severe enough to lead to death despite therapy [1]. Several authors report acute reversible left ventricular function following intravenous administration which is a common route of abuse along with smoking or ingesting the drug [3, 4]. Fortunately our patient was not taking amphetamines during either of her pregnancies, as prenatal exposure has also been associated with cardiomyopathy in the neonate [5].…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that khat chewing can affect the heart leading to acute cardiomyopathy [19,[24][25][26]. This suggestion was…”
Section: Heart Failure and Cardiomyopathiesmentioning
confidence: 99%
“…based on few reports which described the occurrence of acute cardiomyopathy secondary to intravenous amphetamine abuse [24,25], and on one study conducted in Yemen, which involved 50 Yemeni patients with dilated cardiomyopathy who were regular khat chewers. The histopathological study of the heart muscle showed myocyte hypertrophy and interstitial fibrosis [19,26].…”
Section: Vol 1 | Issue 2 | Jul -Dec 2022mentioning
confidence: 99%